Presumptive Identification of Smooth Brucella Strain Antibodies in Canines - Helms, Alyssa B.; Balogh, Orsolya; Franklin-Guild, Rebecca; Lahmers, Kevin; Caswell, Clayton C.; Cecere, Julie T. (Frontiers in Veterinary Science, 2021)
Brucellosis is a zoonotic disease caused by a Gram-negative coccobacillus. There are four Brucella strains of zoonotic importance in our domestic species, subdivided by their culture phenotypes: Brucella abortus (B. abortus), B. melitensis, B. suis (smooth strains) and B. canis (rough strain). Dogs can serve as hosts for all four of the zoonotic strains; however, routine serologic testing in dogs has been limited to the identification of B. canis antibodies. The aim of our study was to identify smooth Brucella strain antibodies in canines. We hypothesize that the Brucella abortus Fluorescence Polarization Assay would be successful in identifying smooth Brucella strain antibodies in canines. Ninety-five dogs, including forty-five hog hunting dogs were screened for circulating antibodies to any of the four zoonotic strains of the bacteria utilizing a combination of Canine Brucella Slide Agglutination Test (CBSA), Brucella canis Agar Gel Immunodiffusion II test (AGID), Brucella abortus Card Agglutination Test (BCA), and the Brucella abortus Fluorescence Polarization Assay (FPA). Test interpretation results yielded a 0% (0/95) smooth Brucella strain seropositivity rate, with 2% (2/95) of dogs yielding inconclusive rough Brucella strain serology results (0-2% rough strain seropositivity rate). Additionally, a retrospective portion of the study was performed to identify sera containing circulating antibodies to any of the smooth strains of Brucella by testing previously banked canine serum samples stored at Cornell’s Veterinary Diagnostic Laboratory from 2018-2019 via Brucella abortus FPA. Of the 769 serum samples tested, 13/769 (1.7%) yielded an inconclusive result, 725/769 (94.2%) were negative, 30/769 (4%) yielded a positive FPA test result, and 1/769 (0.1%) had to be excluded due to insufficient sample remaining to perform the diagnostic test. Of the 30 FPA positive canine serum samples, 97% (29/30) also tested positive on the CBSA test. Additionally, there was a statistically significant (p-value: <0.0001) likelihood of altered (spayed/neutered) and mixed breed dogs to be FPA positive when compared to intact, purebred dogs respectively.